2017
DOI: 10.1108/ijoa-02-2016-0975
|View full text |Cite
|
Sign up to set email alerts
|

Converting values awareness to values enactment through frame-of-reference training

Abstract: Purpose This paper aims to investigate whether values enactment could be increased through frame-of-reference (FOR) training configured around values prototyping and behavioural domain training for managers within an Australian public sector organisation. Design/methodology/approach Employees from an Australian public sector organisation were studied to ascertain the effect of values training and development via a three-way longitudinal design with a control group. Findings The findings indicate that FOR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In organizations, values can be reinforced in several ways such as rewarding employees who follow the right values or adjusting the bureaucratic system to these values (Graber and Kilpatrick, 2008) as well as recruitment and retention of those who share desired values (Deutschman, 2001). Training is one of the most important tools for implementation of values (O’Neill et al , 2017). In large and multifaceted organizations such as armies, there are different agendas and values linked to different entities (Oshry, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In organizations, values can be reinforced in several ways such as rewarding employees who follow the right values or adjusting the bureaucratic system to these values (Graber and Kilpatrick, 2008) as well as recruitment and retention of those who share desired values (Deutschman, 2001). Training is one of the most important tools for implementation of values (O’Neill et al , 2017). In large and multifaceted organizations such as armies, there are different agendas and values linked to different entities (Oshry, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Values training is seen as one of the HR manager's responsibility functions (Charles, 2003), in which the employees are being trained in the specific values the organisation hold, such as tolerance and participative management (Scott, 2005). Research has found that values training, specifically frame-of-reference (FOR) training, increase values enactment clarity and also has a positive effect on the organisational value actions (O'Neill, Travaglione, McShane, Hancock, & Chang, 2017). However, in order to make values training more suitable and effective, it is important to know where the employees are coming from when they enter an organisation, as there is no 'best way' of working with ethics in a diverse organisation.…”
Section: Importance For Human Resource Managementmentioning
confidence: 99%
“…Values training is seen as one of the HR manager's responsibility functions (Charles, 2003), in which the employees are being trained in the specific values the organisation hold, such as tolerance and participative management (Scott, 2005). Research has found that values training, specifically frame-of-reference (FOR) training, increase values enactment clarity and also has a positive effect on the organisational value actions (O'Neill, Travaglione, McShane, Hancock, & Chang, 2017). However, in order to make values training more suitable and effective, it is important to know where the employees are coming from when they enter an organisation, as there is no 'best way' of working with ethics in a diverse organisation.…”
Section: Importance For Human Resource Managementmentioning
confidence: 99%